Sovereign Debt Restructurings: Preemptive or Post-Default - Tamon Asonuma; Christoph Trebesch (Center for Economic Studies and ifo Institute (CESifo), 2015)
Sovereign debt restructurings can be implemented preemptively - prior to a payment default. We code a comprehensive new dataset and find that preemptive restructurings (i) are frequent (38% of all deals 1978-2010), (ii) have lower haircuts, (iii) are quicker to negotiate, and (iv) see lower output losses. To rationalize these stylized facts, we build a quantitative sovereign debt model that incorporates preemptive and post-default renegotiations. The model improves the fit with the data and explains the sovereign's optimal choice: preemptive restructurings occur when default risk is high ex-ante, while defaults occur after unexpected bad shocks. Empirical evidence supports these predictions.
Keywords: F34; F41; H63; 330; sovereign debt; default; debt restructuring; crisis resolution